2016
DOI: 10.1108/bfj-12-2015-0469
|View full text |Cite
|
Sign up to set email alerts
|

Do psychological factors affect green food and beverage behaviour? An application of the theory of planned behaviour

Abstract: Purpose The purpose of this paper is to first integrate incorporated commitment, self-identity, and moral responsibility with the theory of planned behaviour (TPB) to predict the green food and beverage (GFB) behaviours in protecting food environment. Moreover, this study also identified the key influential factors of green behaviours and analysed the mediation effects of commitment in this extended TPB model. Design/methodology/approach The structural equation modelling based on 793 college students was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…Even if food consumption is a personal choice, social influence still plays a salient role in consumption patterns, especially in a Chinese context with typical collectivistic characteristics [ 16 , 18 , 55 ]. Some studies revealed that green purchase intention behaviour is associated with social norms and values, social groups, and cultural influences [ 18 , 56 ]. Consumers follow social norms to receive social acceptance in their groups and to avoid losses from mistaken decisions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if food consumption is a personal choice, social influence still plays a salient role in consumption patterns, especially in a Chinese context with typical collectivistic characteristics [ 16 , 18 , 55 ]. Some studies revealed that green purchase intention behaviour is associated with social norms and values, social groups, and cultural influences [ 18 , 56 ]. Consumers follow social norms to receive social acceptance in their groups and to avoid losses from mistaken decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Consumers follow social norms to receive social acceptance in their groups and to avoid losses from mistaken decisions. Gaining status is an important reason for choosing green or high-quality products [ 18 , 57 ]. This study retrieved statements from participants from the perspective of social influence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors can affect consumer preference for organic agricultural products. Such factors as price [13][14][15], consumers' environmental awareness [16][17][18], social and moral values [19], subjective norms [20,21], perceived behavioral control [20,22] and consumers' trust in organic food [14,23] are considered to be important factors leading to consumers' preference for organic products. Although organic products represent higher quality and better nutrition [24] compared to conventional products, products labeled "organic" are more likely to result in purchase intention [16,25].…”
Section: Literature Reviewmentioning
confidence: 99%